Outpatient Antibiotic Prescribing Among Older Adults in the United States, 2011 to 2014. (4th October 2017) - Kabbani, Sarah; Palms, Danielle; Bartoces, Monina; Stone, Nimalie; Hicks, Lauri
Abstract: Background: Antibiotics are some of the most commonly prescribed medications for older adults, but antibiotic prescribing practices are poorly understood. We analyzed outpatient antibiotic prescribing data for older adults to identify potential targets for antibiotic stewardship. Methods: Outpatient oral antibiotic prescriptions dispensed in the United States for older adults (i.e., ≥ 65 years) between 2011 and 2014 were extracted from the QuintilesIMS Xponent database. The number of prescriptions and U.S. Census denominators were used to calculate prescribing rates. A chi-square for trend test was used to evaluate annual trends in antibiotic prescribing rates. A descriptive analysis of prescribing rates according to antibiotic, age group, sex, state, census region, and provider specialty was completed. Results: In 2011–2014, antibiotic prescribing rates remained stable in U.S. older adults ( P = 0.89). In 2014, older adults were prescribed 51.6 million prescriptions at a rate of 1115 prescriptions/1000 persons. Within this cohort, the rate of prescriptions increased with age; persons aged ≥75 years had a rate of 1157 prescriptions/1000 persons compared with 1084 prescriptions/1000 persons in persons aged 65–74. Rates were highest in the South census region and lowest in the West (1228 vs. 854 prescriptions/1000 persons). Although azithromycin was the most commonly prescribed drug followed by amoxicillin and ciprofloxacin, the most commonly prescribed antibiotic class was the fluoroquinolones (245 prescriptions/1000 persons), followed by penicillins and macrolides. Among individuals aged ≥75 years, ciprofloxacin was the most frequently prescribed drug. Family physicians (23%), followed by internists (20%), prescribed the most antibiotic courses for older adults. Conclusion: On average, U.S. older adults receive enough antibiotic courses for every older individual to receive a prescription each year. Fluoroquinolone use is a potential target for addressing the appropriateness of outpatient antibiotic prescribing practices among older adults. As with antibiotic use in other age groups, efforts to improve antibiotic prescribing may be most needed in the South. Disclosures: All authors: No reported disclosures.